(The product of twice a number and three) can be represented in equation form as: "3 * 2X" and (The difference of five times the number and 3/4) is in equation form: "5X - 3/4"

"Same as" implies equals. So write out the algebraic equation as:

3 ( 2 X ) = (5 X - 3/4)

Solve for X by isolating it:

6X = 5X - 3/4

1X = -3/4

and you have your answer!

"Same as" implies equals. So write out the algebraic equation as:

3 ( 2 X ) = (5 X - 3/4)

Solve for X by isolating it:

6X = 5X - 3/4

1X = -3/4

and you have your answer!